PERTUMBUHAN, PRODUKSI DAN POTENSI GIZI TERONG ASAL ENGGANO PADA BERBAGAI KOMBINASI PERLAKUAN PEMUPUKAN - Titi Juhaeti; Peni Lestari (BERITA BIOLOGI, 2016)
This research was carried out to study growth, production and nutritional potential of two accessions of Enggano eggplant on various combinations of organic and anorganic fertilizer. The experiment was designed using to Factorial Randomized Complete Block with 5 replications. The first factor was two eggplant accessions (Meok accesion/round fruit and Malakoni accession/long finger fruit). The second factor was 9 combinations of organic and inorganic (NPK) fertilizer. The result showed that long finger eggplant more productive than rounded eggplant. The total fruit fresh weight of long finger eggplant (2383.3 g) higher than rounded eggplant (1016.4 g). The ½ NPK + ½ StarTmik fertilization treatment showed better vegetative growth than other treatments. Meanwhile, for total plant production, NPK treatment showed the highest fruit production followed by ½ NPK +½ POKomersial and ½ NPK +½ starTmik treatments.  Nutritional analysis showed that long finger eggplant contained of vitamin C 15.887 g/100g, phosphor 25.983-27.440 mg/100g; calcium 12.340-13.274 mg/100g; fat 0.120-0.277%, carbohydrate 6.244-8.315% and crude fiber 0.872-1.110%. Meanwhile, round eggplant,  contained of vitamin C 10.354 g/100g, phosphor 34.919-37.012 mg/100g; calcium 14.355-15.240 mg/100g; fat 0.275-0.338%,  carbohydrate 6.733-7.896% and crude fiber 2.005-2.211%.